Linear growth determinants of under two years old children in Surabaya, Indonesia - Siti Rahayu Nadhiroh; Hasanah Ayuningtyas; Ika Savitri Salsabil (Elsevier, 2024)
Background: Children under 2 years are in a crucial stage of child development, but they are also vulnerable to nutritional problems, one of which is linear growth faltering. Sociodemographic and health characteristics can influence the linear growth process. This study aimed to analyze the determinants of the linear growth of children under 2 years in four Community Health Centers in Surabaya, Indonesia. Method: A cross-sectional study of 160 parents with children under 2 years was done through consecutive sampling. Sociodemographic and health characteristics were assessed by questionnaires, anthropometric measurements, and secondary data from Maternal and Child Health Book (MCH). The linear growth of the children was identified using length-for-age z-score (LAZ). The data were analyzed using correlation test, One-way ANOVA, independent t-test, and multiple linear regression to see the influential factors. Results: The average LAZ for children under 2 years in four Surabaya City Health Centers areas was normal (−0.76 ± 1.70). Maternal height (p:0.001) and birth length (p:0.001) were significantly related to linear growth. The determinants of linear growth were birth length, maternal height, and history of exclusive breastfeeding, with the most considerable beta value of 0.231 on maternal height. Conclusion: A maternal height primarily determines children under 2 years of linear growth. Parents with growth hormone deficiency were at risk of inheriting this gene to their children. Community Health Centers as health services can be more active in education and nutritional counseling for teenagers and prospective brides.